THE CORRELATION OF ADOLESCENT KNOWLEDGE ABOUT FREE SEX PRACTICES WITH THE RISK OF CERVICAL CANCER ON THE MOTIVATION OF HPV VACCINATION AT JUNIOR HIGH SCHOOL 6 SURABAYA - Arlean, Maria Agatha; Dewanti, Linda; Setyowati, Dewi (UNIVERSITAS AIRLANGGA, 2024)
Background: Cervical cancer had the second position as the leading cause of cancer towards woman in worldwide. The prevalence of cervical cancer in Indonesia reaches 23,4 cases from 100.000 population (Kemenkes RI, 2019). To enhance awareness and knowledge about HPV vaccination and cervical cancer, it is imperative to disseminate information through early health promotion regarding cervical cancer prevention, including HPV vaccination, and avoiding behaviors that may elevate the risk of cervical cancer, such as engaging in unprotected sexual activities. The aim of this study is to determine the correlation between adolescents' knowledge of